تنمية مهارة القراءة الموسعة باللغة العربية بوصفها لغة ثانية : "سلسلة القراءة المتدرجة" أنموذجا - خلدون، ويندي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Researchers have found extensive reading is an effective approach to facilitate language acquisition. Unfortunately, the learners of Arabic as second language especially in Indonesia and Malaysia are less likely to practice it, affecting their ability in learning the Arabic language effectively. This study aimed to explore the importance of extensive reading skills in order to develop language proficiency among Arabic language learners as a second language, to demonstrate the features of Arabic "graded readers", to present how they are used, and to demonstrate their effectiveness in developing extensive reading skills of the learners of Arabic as a second language. It must also be said that there are various methodologies used in this study: analytical descriptive, statistical, and experimental approach. Statistical approach was used to calculate the findings of pretest and post-tests that are carried out, and experimental approach was conducted to determine the effect of the "graded readers" and its activities on the development of the extensive reading skills in Arabic by selecting a sample of 27 students of Islamic high school "Subulussalam" in the city of Padang Indonesia, and 44 students at the Islamic high school "Al-Ameen Gombak" in the state of Selangor Malaysia. This researcher has found that many other researchers have different opinions about the definition of extensive reading, but their differences are just on aesthetic or efferent functions. The results also indicated that the "graded readers" were identified as a valuable material to build the reading skills of Arabic as a second language namely vocabulary acquisition, comprehension and speed reading.